Functionalized polystyrene maleic anhydride copolymer/ZnO nanocomposites for enhanced electrochemical performance. Issue 32 (10th January 2020) - Simon, Remya; Chakraborty, Sohini; Konikkara, Niketha; Mary, N. L.
ABSTRACT: Novel functionalized polymeric materials incorporated with metal oxide nanoparticles are of paramount importance in the field of supercapacitors. These materials provide the advantage of enhanced specific capacitance coupled with efficient energy storage characteristics. In the present study, a new electrode material has been prepared by modifying the polystyrene maleic anhydride copolymer with 4, 4‐diaminodiphenylmethane (DDM). Chemically synthesized zinc oxide nanoparticles were incorporated into the polymer matrix at different weight percentages to form polymer nanocomposites (SMA–DDM–zinc oxide (SDZ)). The effect of increasing the weight percentage of nanoparticles on the modified copolymer was studied in details. The samples were characterized using ultraviolet–visible, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, X‐ray diffraction, and thermogravimetric analysis. SDZ was drop casted on the surface of the glassy carbon electrode and the electrochemical properties were studied. Cyclic voltammetry studies were conducted at various scan rates, and the characteristic curves were observed to be pseudorectangular in nature. The specific capacitance values were measured using the chronopotentiometry technique. SDZ 15% nanocomposite shows an enhanced specific capacitance of 313 F g −1 at a current density of 0.05 A g −1 with a power density of 629 W kg −1 . The superior performance of the SDZ nanocomposite electrodes renders it as a promising material for supercapacitor applications. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48945. Abstract :